2011
DOI: 10.1016/j.jneuroim.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response in MOG35–55 induced EAE

Abstract: Neurological deficit in experimental autoimmune encephalomyelitis (EAE) and multiple sclerosis is widely considered to be a consequence of synergistic T and B cell responses to central nervous system (CNS) antigens. We show that mice immunized with encephalitogenic myelin oligodendrocyte glycoprotein ) peptide develop significant serum levels of anti-MOG antibodies in parallel with disease progression. Furthermore, EAE mice developed antibodies against DNA and RNA, a serological hallmark observed in autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…In addition, we recently demonstrated both the activation of B cells and the generation of specific antibodies against RNA in the MOG -EAE model [19]. Of interest, we also show in this present work that TLR7-deficient mice produce less circulating autoantibodies against RNA and RNA-related antigens such as small nuclear ribonucleoproteins (snRNPs).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, we recently demonstrated both the activation of B cells and the generation of specific antibodies against RNA in the MOG -EAE model [19]. Of interest, we also show in this present work that TLR7-deficient mice produce less circulating autoantibodies against RNA and RNA-related antigens such as small nuclear ribonucleoproteins (snRNPs).…”
Section: Introductionsupporting
confidence: 71%
“…These observations have been attributed to the loss of IL-10-secreting suppressive B cells in the first case and to diminished B-cell support of CD4 + T cells in the latter case [45]. Recently, we demonstrated that direct immunization with MOG 35-55 triggers autoreactive B-cell activation, as exemplified by increased expression levels of CD69 and MHC II molecules by B cells, together with an elevated frequency of B cells within the GCs of secondary lymphoid organs and within the CNS [19]. Thus, reductions in pDC and B-cell frequencies in TLR7-deficient mice may contribute to the protective effect.…”
Section: Discussionmentioning
confidence: 95%
“…Its association with other autoimmune conditions (MG, SLE, ADEM, and pediatric MS) is known for years. Recent studies illustrated that autoimmune response to MOG can induce a NMO-like disease in experimental animal models [5].…”
Section: Discussionmentioning
confidence: 99%
“…remyelination/axon protection) [15] indicating that the detection of antibodies may be useful in assessing the clinical course of the disease. Even though the presence of the antibody response within the CNS in MS patients is well established, the pathogenic role of antibodies still remains obscure and their antigenic targets have yet to be determined [16,17].…”
Section: Introductionmentioning
confidence: 99%